Postural Instability in Subjects With Usher Syndrome - Caldani, Simona; Bucci, Maria Pia; Tisné, Maud; Audo, Isabelle; Van Den Abbeele, Thierry; Wiener-Vacher, Sylvette (Frontiers in Neurology, 2019)
This study investigated postural performances in Usher patients relative to their vestibular impairment. We compared postural performances between three groups: a group of 11 patients with Usher type I (with visual and vestibular impairment), a group of 14 patients with Usher type II (with only visual impairment) and a group of 14 control healthy subjects. Postural stability was measured with a Framiral Multitest Equilibre platform. Three visual conditions (open eyes (EO), closed eyes (EC) and vision disturbed by optokinetic stimulation (OPT) were performed during two different postural conditions standing on stable and standing unstable platform. The surface and mean velocity of the center of pressure displacement (CoP) were measured and a postural instability index (PII) was calculated. Usher (type I and II) were more instable than control subjects only for unstable platform. Patients with Usher type I (with severe vestibular impairment) were also significantly more unstable than patients with Usher type II (with normal vestibular function) on unstable platform. We found also a correlation between the severity of the vestibular impairment and the surface of the CP displacement. We suggest that poor postural control of Usher patients is due to their abnormal visual and/or vestibular inputs. Measurements of postural stability on unstable platform can differentiate patients with Usher type I versus type II. We emphasized the importance of multisensory evaluation in these patients to develop specific visuo-vestibular rehabilitation techniques to improve their postural stability and improve their life quality.